1,3,4-Oxadiazole Scaffold in Antidiabetic Drug Discovery: An Overview - Gupta, Ojasvi; Chawla, Gita; Pradhan, Tathagata (Mini Reviews in Medicinal Chemistry, 2024)
Diabetes mellitus is one of the biggest challenges for the scientific community in the 21st century. With the increasing number of cases of diabetes and drug-resistant diabetes, there is an urgent need to develop new potent molecules capable of combating this cruel disease. Medicinal chemistry concerns the discovery, development, identification, and interpretation of the mode of action of biologically active compounds at the molecular level. Oxadiazole-based derivatives have come up as a potential option for antidiabetic drug research. Oxadiazole is a five-membered heterocyclic organic compound containing two nitrogen atoms and one oxygen atom in its ring. Oxadiazole hybrids have shown the ability to improve glucose tolerance, enhance insulin sensitivity, and reduce fasting blood glucose levels. The mechanisms underlying the antidiabetic effects of oxadiazole involve the modulation of molecular targets such as peroxisome proliferator-activated receptor gamma (PPARγ), α-glucosidase, α-amylase and GSK-3β which regulate glucose metabolism and insulin secretion. The present review article describes the chemical structure and properties of oxadiazoles and highlights the antidiabetic activity through action on different targets. The SAR for the oxadiazole hybrids has been discussed in this article, which will pave the way for the design and development of new 1,3,4-oxadiazole derivatives as promising antidiabetic agents in the future. We expect that this article will provide comprehensive knowledge and current innovation on oxadiazole derivatives with antidiabetic potential and will fulfil the needs of the scientific community in designing and developing efficacious antidiabetic agents.
Keywords: SAR